Consumer Satisfaction Analysis Reviewed From Store Atmosphere, Product Variation and Service Quality - Vandhega, Bintang Ghivary Rama; Wiyadi, Wiyadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Along with the development of the culinary industry, especially in the coffee shop sector, there is an increase in very tight competition between various businesses in this field. To attract customers and maintain their loyalty, every coffee shop needs to pay attention to various factors that can affect consumer experience, one of which is store atmosphere. In addition, the variety of products offered and the quality of service provided are also important elements in creating customer satisfaction. Therefore, this study aims to identify and analyze the effect of store atmosphere, product variety, and service quality on customer satisfaction at Coffee Shops in Manahan. This type of research is quantitative research, with a sample of 100 respondents. This research is quantitative research. The data required is primary data obtained through a questionnaire with a Likert scale. The population of the study was Coffee Shop customers in Manahan, with a sample of 100 respondents taken using the convenience purposive sampling technique. Data analysis was carried out through several stages, namely validity testing to ensure the validity of the questionnaire, reliability testing to measure the consistency of respondents' answers, classical assumption testing which includes normality, multicollinearity, and heteroscedasticity tests, and multiple linear regression analysis to test the effect of independent variables on dependent variables, both simultaneously and partially. The results show that partially the variables store atmosphere, product variation, and service quality have a positive and significant effect on customer satisfaction. The coefficient of determination (R2) obtained a result of 0.588, meaning that the variables store atmosphere (X1), product variation (X2) and service quality (X3) are able to explain the variation of the customer satisfaction variable (Y) by 0.588 or 58.8%, and the rest is explained by other variables that are not included in the model.